2011
DOI: 10.1089/ten.tea.2010.0346
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cells Immunomagnetically Selected For CD271+ Antigen PromoteIn Vitrothe Repair of Articular Cartilage Defects

Abstract: Synovial membranes from OA patients contain more cells expressing CD271 antigen than those from healthy joints, and spontaneous cartilage repair tissue contains cells positive for CD271 antigen. These data suggest the involvement of CD271 antigen in spontaneous cartilage repair and indicate that the cell subset MSC CD271+ provides higher quality chondral repair than the CD271- subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
(50 reference statements)
3
33
0
Order By: Relevance
“…CD271 has been strongly linked to chondrogenesis in several studies. When MSCs were isolated with conventional plastic adhesion, the CD271+ portion was superior to the CD271-portion of MSCs in cartilage matrix deposition, tissue formation and integration with the native cartilage in an in vitro cartilage repair model [Hermida-Gómez et al, 2011]. In human synovium, CD271+ cells are more chondrogenic than CD73+ and CD106+ subpopulations [Arufe et al, 2010].…”
Section: Discussionmentioning
confidence: 97%
“…CD271 has been strongly linked to chondrogenesis in several studies. When MSCs were isolated with conventional plastic adhesion, the CD271+ portion was superior to the CD271-portion of MSCs in cartilage matrix deposition, tissue formation and integration with the native cartilage in an in vitro cartilage repair model [Hermida-Gómez et al, 2011]. In human synovium, CD271+ cells are more chondrogenic than CD73+ and CD106+ subpopulations [Arufe et al, 2010].…”
Section: Discussionmentioning
confidence: 97%
“…These properties hold MSCs as a promising candidate for the development of new therapeutics for the application in regenerative medicine [Kode et al, 2009] and tissue engineering in order to accelerate wound healing [Maxson et al, 2012] and for articular cartilage treatment [Hermida-Gómez et al, 2011]. It has been proven that MSCs can be harvested from many human tissues, such as the bone marrow [Prockop, 1997;Caplan and Bruder, 2001], adipose tissue [Zuk et al, 2001] and skin [Toma et al, 2005;Lorenz et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Since the CD271 antigen is able to promote cell proliferation and differentiation along three mesenchymal lineages, i.e. adipogenic, osteogenic and chondrogenic [27,28,[38][39][40], it has been intensely investigated as an antigen driving generation of differentiated cells suitable for specific therapeutic applications. Obtaining the chondrocyte-like phenotype in an attempt to regenerate cartilage has been one of these experimental directions.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining the chondrocyte-like phenotype in an attempt to regenerate cartilage has been one of these experimental directions. Because it was found that the CD271 + MSCs can effectively differentiate towards cartilage tissue [15,27,28], we decided to check if these cells can differentiate into chondrocyte-like cells of the nucleus pulposus (NP) of IVD. However, since CD271 is a very efficient nerve growth factor receptor, its presence may lead to nerve ingrowth into NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation